Electron tunneling in chemistry : chemical reactions over large distances - Khairutdinov, R. F. (Rafail Fattakhovich) (Comprehensive chemical kinetics, 1989)
In Volume 30, an attempt is made to consider comprehensively both theoretical and experimental data that have been obtained to date on electron tunneling reactions involving chemical compounds of various classes, and to discuss the role played by these reactions in different areas of chemistry. The discussion of the above problem is preceded by a review of data on tunneling phenomena in nuclear physics, atomic physics, solid-state physics, as well as on the tunneling effects in chemistry that go beyond the framework of the main subject of this monograph. This review is included to acquaint the reader with the role of tunneling phenomena in physics and chemistry as a whole, to show how diversified the kingdom of tunneling phenomena is, and to see more distinctly the similarities and the differences between electron tunneling in chemical reactions and other tunnel phenomena.